Cucurbit Genomics Database (CuGenDB): a central portal for comparative and functional genomics of cucurbit crops. Issue Volume 47:Issue D1(2019) (13th October 2018) - Zheng, Yi; Wu, Shan; Bai, Yang; Sun, Honghe; Jiao, Chen; Guo, Shaogui; Zhao, Kun; Blanca, Jose; Zhang, Zhonghua; Huang, Sanwen; Xu, Yong; Weng, Yiqun; et al.
Abstract: The Cucurbitaceae family (cucurbit) includes several economically important crops, such as melon, cucumber, watermelon, pumpkin, squash and gourds. During the past several years, genomic and genetic data have been rapidly accumulated for cucurbits. To store, mine, analyze, integrate and disseminate these large-scale datasets and to provide a central portal for the cucurbit research and breeding community, we have developed the Cucurbit Genomics Database (CuGenDB;http://cucurbitgenomics.org ) using the Tripal toolkit. The database currently contains all available genome and expressed sequence tag (EST) sequences, genetic maps, and transcriptome profiles for cucurbit species, as well as sequence annotations, biochemical pathways and comparative genomic analysis results such as synteny blocks and homologous gene pairs between different cucurbit species. A set of analysis and visualization tools and user-friendly query interfaces have been implemented in the database to facilitate the usage of these large-scale data by the community. In particular, two new tools have been developed in the database, a 'SyntenyViewer' to view genome synteny between different cucurbit species and an 'RNA-Seq' module to analyze and visualize gene expression profiles. Both tools have been packed as Tripal extension modules that can be adopted in other genomics databases developed using the Tripal system.